2023
DOI: 10.1002/hsr2.1674
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV, hepatitis B virus, hepatitis C virus, drug use, and sexual behaviors among street children in Iran: A systematic review and meta‐analysis

Naser Nasiri,
Polychronis Kostoulas,
Payam Roshanfekr
et al.

Abstract: Background and AimsStreet children face a disproportionately higher risk of human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) due to high‐risk sexual and drug use practices. We aimed to estimate the prevalence of these infections and related risk behaviors among street children in Iran.MethodsWe searched PubMed, Web of Science (ISI), Embase, Scopus, and Google Scholar for the English‐language records and Iranian databases, including SID, Magiran, and IRANDOC for the Farsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(98 reference statements)
0
0
0
Order By: Relevance
“…This indicates the increasing burden of viral hepatitis complicating VL patients that would affect the treatment outcomes resulting in disease severity and mortality. Although there was no previous data about the pooled prevalence of HBV and HCV on VL patients, systematic review and meta-analysis studies reported a combined prevalence of HBV and HCV; 13.7 and 24.7% ( Yu et al, 2020 ), 10.5 and 5.4% ( Kenfack-Momo et al, 2022 ), 4.8 and 1.0% ( Wu et al, 2023 ), 2.66 and 44.82% ( Aghaei et al, 2023 ), 1.97 and 1.88% ( Nasiri et al, 2023 ), and 2.89 and 21.57% ( Mehmandoost et al, 2022 ), respectively. This variation is due to the difference in study populations, hepatitis burden in geographic location, and healthcare provision systems.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the increasing burden of viral hepatitis complicating VL patients that would affect the treatment outcomes resulting in disease severity and mortality. Although there was no previous data about the pooled prevalence of HBV and HCV on VL patients, systematic review and meta-analysis studies reported a combined prevalence of HBV and HCV; 13.7 and 24.7% ( Yu et al, 2020 ), 10.5 and 5.4% ( Kenfack-Momo et al, 2022 ), 4.8 and 1.0% ( Wu et al, 2023 ), 2.66 and 44.82% ( Aghaei et al, 2023 ), 1.97 and 1.88% ( Nasiri et al, 2023 ), and 2.89 and 21.57% ( Mehmandoost et al, 2022 ), respectively. This variation is due to the difference in study populations, hepatitis burden in geographic location, and healthcare provision systems.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the increasing burden of viral hepatitis complicating VL patients that would affect the treatment outcomes resulting in disease severity and mortality. Although there was no previous data about the pooled prevalence of HBV and HCV on VL patients, systematic review and meta-analysis studies reported a combined prevalence of HBV and HCV; 13.7 and 24.7% (Yu et al, 2020), 10.5 and 5.4% (Kenfack-Momo et al, 2022), 4.8 and 1.0% (Wu et al, 2023), 2.66 and 44.82% (Aghaei et al, 2023), 1.97 and 1.88% (Nasiri et al, 2023), and 2.89 and 21.57% (Mehmandoost et al, 2022), respectively. This variation is due to the difference in study populations, hepatitis burden in geographic location, and healthcare provision systems.…”
Section: Discussionmentioning
confidence: 99%